Improving Students` Speaking Skill by Using Retelling Story through Pantomime at The Second Semester of English Study Program University of Papua - Suardi Sahid; Sukristiningsih Sukristiningsih; Ruslan Ruslan (Qalam : Jurnal Ilmu Kependidikan, 2022)
This research focuses on the improvement of students` Speaking skills at Papua University by retelling stories through pantomime. This article focused on two research questions; is pantomime effective to improve the students` speaking at English Study Program? And are the students interested in learning speaking through pantomime? This researcher applied experimental research with pre-test and post-test design. This research was undertaken at the second semester English Study program. The numbers of population were 120 students and the researcher took 33 students from class A as samples using the purposive sampling technique. The researcher used questionnaires as instruments of the data collection. The result of this research shows that there were significant developments in students` speaking skills at the second semester English study Program at Papua University after conducting the treatments by using Retelling Story through Pantomime. In which the score of the t-test (6,23) is bigger than the score of the t-table (2,03). It means that Retelling Story through pantomime gives significant improvement to the students` speaking skills. In addition, the researcher found almost all of the students gave positive responses toward retelling stories through pantomime in improving speaking skills. Keywords: Retelling Story, Pantomime, and Speaking Skill.